2017
DOI: 10.1097/cji.0000000000000148
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing Treatment in BRAF V600 Mutant Melanoma: Anti-PD-1 Before and After BRAF Inhibition

Abstract: Novel agents targeting immune checkpoint molecules or mutated BRAF are active therapeutic options for patients with BRAF-mutant melanoma. However, the most effective first-line treatment and the optimal sequencing of these agents have not been well characterized. To explore this, we retrospectively assessed 114 patients from 4 centers with advanced, BRAF-mutant melanoma who received anti-programmed cell death-1 (PD-1)/PD-L1 antibodies. We evaluated clinical outcomes, including objective response rate (ORR), ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
3
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 23 publications
1
60
3
2
Order By: Relevance
“…In our cohort, patients with BRAFV600E/K mutation received predominantly targeted therapy, and in this subgroup, 63% of patients had a response (CR or PR). This was slightly higher than previously published [43], but in our cohort, only 21 patients with BRAFV600E/K mutation received second-line therapy, and therefore the outcomes need to be interpreted cautiously. Nevertheless, our group and others have already demonstrated that patients with BRAFV600E/K first-line immunotherapy followed by targeted therapy, similar to what patients in this cohort received, seem to have better outcomes than the inverse sequence [44,45].…”
Section: Discussioncontrasting
confidence: 61%
“…In our cohort, patients with BRAFV600E/K mutation received predominantly targeted therapy, and in this subgroup, 63% of patients had a response (CR or PR). This was slightly higher than previously published [43], but in our cohort, only 21 patients with BRAFV600E/K mutation received second-line therapy, and therefore the outcomes need to be interpreted cautiously. Nevertheless, our group and others have already demonstrated that patients with BRAFV600E/K first-line immunotherapy followed by targeted therapy, similar to what patients in this cohort received, seem to have better outcomes than the inverse sequence [44,45].…”
Section: Discussioncontrasting
confidence: 61%
“…The sequence of treatment for a patient with targeted therapy and immune therapy is not well established. Starting a patient on a BRAF inhibitor or anti-PD1 inhibitor is effective regardless of the treatment order, but more randomized controlled trials are required to address and establish the superiority and sequencing of one therapy over the other [67,68]. Studies have also shown that the efficacy of immunotherapy is improved in previously untreated patients compared to patients who have single agent immunotherapy failure or failure to targeted therapy [69].…”
Section: Acquired Resistancementioning
confidence: 99%
“…BRAF and MEK mutations contribute to dysfunction of the Ras-Raf-MEK-ERK Map kinase mutations that are present in greater than 90% of melanomas. Specific BRAF mutations when pretreated with Dabrafenib have been associated with reduced response to PD-1/PD-L1 inhibition in melanoma [5355]. However, when Dabrafenib was combined with MEK suppressor Tremelimumab, an improved response to PD-L1 inhibition was noted [55, 56].…”
Section: Factors Influencing Pd-l1 Expressionmentioning
confidence: 99%